2021
DOI: 10.3892/ol.2021.12922
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between p53 status and the bioeffect of ionizing radiation (Review)

Abstract: Radiotherapy is widely used in the clinical treatment of cancer patients and it may be used alone or in combination with surgery or chemotherapy to inhibit tumor development. However, radiotherapy may at times not kill all cancer cells completely, as certain cells may develop radioresistance that counteracts the effects of radiation. The emergence of radioresistance is associated with the genetic background and epigenetic regulation of cells. p53 is an important tumor suppressor gene that is expressed at low l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 86 publications
(80 reference statements)
1
27
0
Order By: Relevance
“…Several studies have defined P53 as a key molecule involved in radioresponse of cells, since it is linked to radiotherapy efficacy, [50][51][52] and is considered as a biomarker for clinical radiosensitivity. 53 Radiation-induced expression of P53 has been demonstrated in glioblastoma and hepatocellular carcinoma cells, 54,55 similar to our results that indicated upregulation of P53 by 7-geranyloxycoumarin and radiation. Hence, observed combinatorial effects in present study could also be explained by changes induced in the expression of BMI-1, NF-κB (REL-A), and P53.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have defined P53 as a key molecule involved in radioresponse of cells, since it is linked to radiotherapy efficacy, [50][51][52] and is considered as a biomarker for clinical radiosensitivity. 53 Radiation-induced expression of P53 has been demonstrated in glioblastoma and hepatocellular carcinoma cells, 54,55 similar to our results that indicated upregulation of P53 by 7-geranyloxycoumarin and radiation. Hence, observed combinatorial effects in present study could also be explained by changes induced in the expression of BMI-1, NF-κB (REL-A), and P53.…”
Section: Discussionsupporting
confidence: 89%
“…USP7 was reported to bind to the carboxy-terminus of p53, while p53 specifically recognizes the N-terminal tumor necrosis factor-receptor associated factor (TRAF)-like domain of USP7 [ 22 , 23 ]. p53, as the most frequently mutated genes in LSCC, plays a pivotal role in tumorigenesis, cell growth rates, and even tumor response to chemotherapy and radiation [24] , [25] , [26] . The mechanism of how p53 status affects the cellular response to radiotherapy involves signaling pathways in cell survival, growth, apoptosis, ferroptosis, and DNA repair [27] , [28] , [29] .…”
Section: Discussionmentioning
confidence: 99%
“…It was also confirmed that cell lines from head and neck cancer harboring disruptive p53 mutations were more radioresistant than those with p53-wild type or non-disruptive p53 mutations [31] . However, many studies reported that mutant p53 had no effect or even enhanced cellular sensitivity to radiation [32] . It is quite important to be aware that p53 could present different types of mutations, and other p53 mutations do not have the same biological effects, which need to be explored furtherly.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, high-LET radiation induced apoptosis without significant increase in p53 or p21/waf1 in these cells [ 167 ]. Mutations in p53 are associated with resistance to radiation-induced cell death and resistance to cell cycle regulation, especially mutations that affect p53 regulation of p21/waf1 [ 168 ]. Niemantsverdriet et al compared p53 phosphorylation at S37 (apoptotic signaling) and S315 (fibrotic signaling) by high- and low-LET radiation, and downstream regulation of the pro-fibrotic gene plasminogen activator inhibitor 1 (PAI-1) in transformed lung epithelial cells (A549) and immortalized, non-transformed human embryonic kidney cells (HEK) [ 169 ].…”
Section: Signal Transduction By High and Low Letmentioning
confidence: 99%